VARIABEL-VARIABEL FUNDAMENTAL YANG BERPENGARUH PADA KEBIJAKAN DIVIDEN - Pati, I Gst Ngr Agung Bayu; Astika, Ida Bgs. Putra (E-Jurnal Akuntansi, 2016)
The purpose of t his study uses the fundamental variables in terms of financial ratios in predicting dividend policy. The research sample was determined by census method that is as much as 15 (fifteen) companies included in the food and beverage industry are listed (listing) in Indonesia Stock Exchange with a listing from 2010 until 2012. Based on the discussion, the importance of the conclusion of the results the research is as follows: Free Cash Flow and no significant negative effect on dividend policy, Return on Equity significant negative effect on dividend policy, Debt to Equity Ratio and no significant positive effect on dividend policy, and the Net Profit Margin positive and significant impact on dividend policy food and beverage industry to go public in Indonesia Stock Exchange.
Keywords: fundamental variables; dividend policy; stock exchange